EFEKTIFITAS KINERJA MANAJEMEN BERBASIS SEKOLAH DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD PADA PENINGKATAN MUTU SMP AL AZHAR SYIFA BUDI LEGENDA - Sunaryati; Mustofa; Sarwo Edy; Sumarta (STIT Sirojul Falah Bogor, 2023)
The education system is required to be able to produce maximum output by carrying out an effective process that is continuous between input, process and output as desired with a better governance system or known as school-based management, where SBM expects schools to be more independent and able to freely develop and improve the quality of performance. This study aims to determine the effectiveness of school management at SMP Al Azhar Syifa Budi Legenda by using a balanced scorecard performance measurement with four perspectives, namely a financial perspective, a customer perspective, an internal business process perspective and a growth and learning perspective. This research is a qualitative descriptive research. Primary data in the form of a questionnaire is used to measure the performance of the customer perspective and the perspective of growth and learning. In terms of performance, SMP Al Azhar Syifa Budi Legenda as a whole is in the good category. The results of measuring the performance analysis of the balanced scorecard on a financial perspective at SMP Al Azhar Syifa Budi Legenda show good performance and show financial performance that is economical, effective and quite efficient. The measurement results of performance analysis on the customer perspective show a pretty good performance. Keywords: Effectiveness, MBS, Balanced Scorecard